Bacillus anthracis Protective Antigen Kinetics in Inhalation Spore-Challenged Untreated or Levofloxacin/Raxibacumab-Treated New Zealand White Rabbits - Corey, Alfred (MDPI, 2013)
Inhaled Bacillus anthracis spores germinate and the subsequent vegetative growth results in bacteremia and toxin production. Anthrax toxin is tripartite: the lethal factor and edema factor are enzymatic moieties, while the protective antigen (PA) binds to cell receptors and the enzymatic moieties. Antibiotics can control B. anthracis bacteremia, whereas raxibacumab binds PA and blocks lethal toxin effects. This study assessed plasma PA kinetics in rabbits following an inhaled B. anthracis spore challenge. Additionally, at 84 h post-challenge, 42% of challenged rabbits that had survived were treated with either levofloxacin/placebo or levofloxacin/raxibacumab. The profiles were modeled using a modified Gompertz/second exponential growth phase model in untreated rabbits, with added monoexponential PA elimination in treated rabbits. Shorter survival times were related to a higher plateau and a faster increase in PA levels. PA elimination half-lives were 10 and 19 h for the levofloxacin/placebo and levofloxacin/raxibacumab groups, respectively, with the difference attributable to persistent circulating PA-raxibacumab complex. PA kinetics were similar between untreated and treated rabbits, with one exception: treated rabbits had a plateau phase nearly twice as long as that for untreated rabbits. Treated rabbits that succumbed to disease had higher plateau PA levels and shorter plateau duration than surviving treated rabbits.